The Strategic Role of Indonesian Language Teachers in Increasing Students' Learning Motivation - Putri Wulan Dhari; Mawaddah (STMIK Indonesia Banda Aceh, 2025)
Motivation to learn is very necessary in learning activities for the realization of learning success. However, reality implies that many students have low learning motivation. This situation can be seen from various student attitudes, such as not focusing, not interacting enough with the teacher, not being active, and so on. Students' learning motivation has a close correlation with the teacher's role in designing and organizing learning activities, especially in Indonesian language lessons which tend to be considered boring. The teacher is the determining factor in order to revive the enthusiasm of students in participating in learning activities. Based on this explanation, this research aims to find out and describe the role of teachers in increasing students' learning motivation in learning Indonesian. This research is descriptive qualitative research with the research subjects being the principal, 5 class teachers, and 10 students. Data was collected through observation, interviews and documentation. Data collection, data reduction, data presentation, and drawing conclusions are needed in data analysis. The research results show that teachers have tried to fulfill their role in increasing students' learning motivation in learning Indonesian at MIN 6 Central Aceh. However, it is still found that the role of teachers has not been fulfilled optimally. Therefore, reflection and evaluation are needed from teachers so that the teacher's role can be carried out more optimally so that students' learning motivation can be maximized.